2013
DOI: 10.1016/j.bbmt.2012.10.029
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Stem Cell Transplantation for Refractory or Poor-Risk Relapsed Hodgkin's Lymphoma: Effect of the Specific High-Dose Chemotherapy Regimen on Outcome

Abstract: More active high-dose chemotherapy (HDC) regimens are needed for refractory Hodgkin's lymphoma (HL). We report a cohort analysis of 180 consecutive patients with primary refractory or poor-risk relapsed HL treated with busulfan-melphalan (Bu-Mel) (n = 39), gemcitabine-busulfan-melphalan (Gem-Bu-Mel) (n = 84), or BEAM (BCNU, etoposide, ara-C, melphalan; n = 57) between 2005 and 2010. Their pre-HDC positron emission tomography (PET) scans were interpreted prospectively. Despite more prevalent poor-risk features … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
58
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 21 publications
(30 reference statements)
5
58
1
3
Order By: Relevance
“…32 The Houston team showed independent adverse effect (Hazard ratio 3.1) of positive PET at transplant in 180 poor-risk relapsing or refractory HL patients. 51 Devillier et al also recently reported in 111 patients with relapsed or refractory HL that only PET status significantly influenced OS in multivariate analysis, regardless of disease risk at relapse. 52 On the other hand, the same studies emphasize that a substantial proportion of patients with positive PET before HDT will remain free of subsequent relapse, indicating that some patients could be cured despite a hypermetabolic residual mass after salvage therapy, but also that interpretation criteria could probably be improved to maximize FDG-PET positive predictive value in this setting.…”
Section: Definition Of Chemosensitivitymentioning
confidence: 89%
“…32 The Houston team showed independent adverse effect (Hazard ratio 3.1) of positive PET at transplant in 180 poor-risk relapsing or refractory HL patients. 51 Devillier et al also recently reported in 111 patients with relapsed or refractory HL that only PET status significantly influenced OS in multivariate analysis, regardless of disease risk at relapse. 52 On the other hand, the same studies emphasize that a substantial proportion of patients with positive PET before HDT will remain free of subsequent relapse, indicating that some patients could be cured despite a hypermetabolic residual mass after salvage therapy, but also that interpretation criteria could probably be improved to maximize FDG-PET positive predictive value in this setting.…”
Section: Definition Of Chemosensitivitymentioning
confidence: 89%
“…Toxicity seemed equivalent between regimens; however, there were better survival results with GemBuM. 86 …”
Section: Conditioning Regimens For Lymphoma G Damaj Et Almentioning
confidence: 99%
“…A BEAM-nál hatékonyabb és kevésbé toxikus busulfanalapú kondicionáló kezelést keresve Nieto és mtsai a busulfan-melphalan, a gemcitabin-busulfanmelphalan és a BEAM-kezelések hatékonyságát hasonlí-tották össze. A leghatékonyabbnak a gemcitabin-busulfan-melphalan bizonyult, az eseménymentes túlélés (EFS) 87%, a teljes túlélés (OS) pedig 82% volt [17]. Történtek vizsgálatok a carmustin helyett nagy dózisú bendamustin, fotemustin alkalmazásával, de a kis betegszám (15, illetve 20 HL-beteg) miatt még nem értékel-hetőek egyértelműen [18,19].…”
Section: Kondicionáló Kezelésekunclassified